Development of an SMS-based library querying system for the UP Integrated School Library - Cadiz, Paolo Leandro S.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
With the current pace in development of mobile technologies, more people are starting to demand for mobile services. Librarians are no exemption from this demand, as seen in mobile journals and online articles, the demand for mobile library services is increasing, with people requesting that book searching and borrowing, as well as reference querying be made mobile for easy access wherever they go. The viable solution to the library users' demand is the use of Short Messaging Services, or text messaging as a medium to deliver these mobile library services.
The technology for SMS-based mobile library services already exists, with current software and web applications such as MOSIO and SYRSIDYNIX already enabling certain libraries to provide mobile book searching and reference querying. However, these current technologies are proprietary, and come with a price and certain restrictions that impose limitations on the improvement of library services. This leads to only a few libraries availing of the service and providing the demanded mobile library services. A general solution to the issue would be the development of an open-source mobile library service system that can compensate for the limitations of the proprietary systems.
The research thus aims to determine the requirements of developing an open-source SMS-based library querying system, which will provide similar functions, as well as answer to the limitations of the current proprietary systems. The research also specifically aims to be able to develop the mobile library system based on the determined requirements. The product of the research is an open-source mobile library querying system that will perform the functions of currently existing systems, as well as remove the imposed limitations to libraries.
The research was conducted alongside the Waterfall Model of Systems Analysis and Design, and progresses on the first three stages: (1) Requirement Gathering, (2) System Design and (3) Implementation. A pre-test survey was conducted to determine the possible user requirements of the system. Once determined, the system was designed and developed based on the user requirements to determine the technical requirements, and then was implemented on a local database for further testing.
The research was able to find out the following requirements
A perceived need for the services provided by the system by the library users
The use of open-source alternatives to eliminate the limitations of existing proprietary systems; and
The capability of the system to improve as needed by the library and its users.
The system developed was able to answer to the needs presented, and will prove to be an enhancement to current library services provided by the libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Integrated School Library; Mobile communication systems -- Library applications -- Philippines -- Quezon City; Application software -- Development